2019
DOI: 10.1021/acsphotonics.9b00907
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Wetting Layer-Free Plasmonic Gold Films

Abstract: Ultrathin gold films are attractive for plasmonic and metamaterial devices, thanks to their useful optical and optoelectronic properties. However, deposition of ultrathin continuous Au films of a few nanometer thickness is challenging and generally requires wetting layers, resulting in increased optical losses and incompatibility with optoelectronic device requirements. We demonstrate wetting layer-free plasmonic gold films with thicknesses down to 3 nm obtained by deposition on substrates cooled to cryogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 49 publications
(74 reference statements)
0
29
0
5
Order By: Relevance
“…Importantly, we introduced a hydrogen-plasma post-deposition treatment to further alter the optical properties of TiN while maintaining the thermal budget at the low temperature of 250 • C. We found that such plasma treatments greatly improved the metallic quality of the films, increasing the ε 1 slope by 1.3 times, from −0.015 to −0.021, on MgO and two times, from −0.012 to −0.024, on Si (100) for 11 nm thick films. Our work demonstrates the feasibility of developing metallic and plasmonic ultrathin TiN films with a PE-ALD deposition and post-deposition treatment that is substrate insensitive and with a low temperature of 250 • C. Our work opens up potentials of investigating a CMOS compatible ultrathin plasmonic material, which have been of interest for flexible transparent optoelectronic devices [19,20] and nonlinear optical applications [21,22].…”
Section: Introductionmentioning
confidence: 87%
“…Importantly, we introduced a hydrogen-plasma post-deposition treatment to further alter the optical properties of TiN while maintaining the thermal budget at the low temperature of 250 • C. We found that such plasma treatments greatly improved the metallic quality of the films, increasing the ε 1 slope by 1.3 times, from −0.015 to −0.021, on MgO and two times, from −0.012 to −0.024, on Si (100) for 11 nm thick films. Our work demonstrates the feasibility of developing metallic and plasmonic ultrathin TiN films with a PE-ALD deposition and post-deposition treatment that is substrate insensitive and with a low temperature of 250 • C. Our work opens up potentials of investigating a CMOS compatible ultrathin plasmonic material, which have been of interest for flexible transparent optoelectronic devices [19,20] and nonlinear optical applications [21,22].…”
Section: Introductionmentioning
confidence: 87%
“…Reproduced with permission. [ 48 ] Copyright 2015, American Chemical Society. c) SEM images of Ag and oxygen‐doped Ag layers of different thicknesses on ZnO films.…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmsmentioning
confidence: 99%
“…Studies have shown that substrate cooling is indeed beneficial for high‐quality, ultrathin metal film formation. [ 48,96,160 ] Lemasters et al. have found that by cooling the substrate to cryogenic temperatures (≈−195 °C), wetting‐layer‐free plasmonic Au films with thicknesses down to 3 nm can be obtained.…”
Section: Fabrication Of High‐quality Ultrathin Metal Filmsmentioning
confidence: 99%
See 2 more Smart Citations